Manajemen Strategis Berbasis Balanced Scorecard dalam Peningkatan Kinerja Layanan Publik di PT Pelindo Regional 4 Makassar - Nasir, Nasir (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2025)
This research is motivated by the importance of implementing effective strategic management in improving the quality of public services in State-Owned Enterprises (SOEs), especially in the port sector. PT Pelindo Regional 4 Makassar as a strategic public service provider faces demands to improve efficiency, customer satisfaction, and competitiveness. This study aims to analyze the application of strategic management based on Balanced Scorecard in improving public service performance. The approach used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that the Balanced Scorecard has been applied through four main perspectives, namely finance, customers, internal business processes, and learning and growth. This implementation has a positive impact on operational efficiency, increasing customer satisfaction, improving work processes, and developing human resources. However, challenges are still found in the aspect of equitable distribution of training and information system integration. The recommendations of this study are the importance of strengthening coordination across units, periodic evaluation of performance indicators, and increasing investment in information technology systems and employee training. With consistent implementation, the Balanced Scorecard can be an effective strategic tool to support superior and sustainable public services